Integrated Framework to Enhance Knowledge Management Capabilities: A Case Study of Vocational Institution - Fahadha, Rizqa Ula; Muhammad Syamsul Maárif; Budi Yulianto (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2025)
Knowledge management plays a crucial role in enhancing institutional competitiveness within the rapidly evolving knowledge-based economy. This study aims to formulate effective knowledge manage-ment strategies for the Applied Manufacturing Engineering Undergraduate Program at T University, which faces structural challenges, including an aging faculty demographic and audit findings indicating low competitiveness. A quantitative, descriptive-analytical approach was employed, integrating the American Productivity and Quality Centre (APQC) model, the Analytical Hierarchy Process (AHP), and the TAIDA (Tracking, Analyzing, Imaging, Deciding, Acting) framework. The APQC model assessed knowledge management maturity, AHP identified strategic priorities, and TAIDA guided scenario deve-lopment. Findings reveal four strategic priorities are developing an integrated digital platform, strengthening industry collaboration and co-creation, optimizing local and tacit knowledge, and imple-menting community-based governance. The integrated APQC–AHP–TAIDA approach improved knowl-edge flow efficiency, bridged intergenerational gaps, and enhanced competitiveness through adaptive go-vernance. The study concludes by recommending a digital evaluation model for curriculum and research partnerships, as well as human resource regeneration policies oriented toward sustainable vocational knowledge management.